THE INFLUENCE OF SERVICE QUALITY (SERVQUAL) ON CONSUMER SATISFACTION OF ISLAMIC EDUCATION SERVICES BUSINESS (PONDOK PESANTREN) - Jamilah, Dinny; Fauziyah, Azizah; Koeswandi, Tika Annisa Lestari (A Social Science and Entrepreneurship Journal, 2022)
The purpose of this study was to determine the effect of service quality on consumer satisfaction in the Islamic Education Service Business (Pondok Pesantren). The approach in this study is a quantitative approach, the data source used is primary data, namely data obtained directly from respondents via google form, secondary data, namely information from related agencies and literature studies as well as various journals and research reports related to the research topic. The results of this study are Service Quality has a positive effect on Consumer Satisfaction in the Islamic Education Service Business (Pondok Pesantren) at the Esalama Female Dormitory of Cipasung Islamic Boarding School.